Observer l’usage de l’espace (dans des espaces vides). Un séjour de terrain au Mexique en temps de coronavirus - Victor Anduze Rivero (EchoGéo)
In this article, I will describe the (aborted) field research in Mexico that I carried out in March 2020 as part of my research work to validate my Master 2 Research in development studies at the Institute of Development Studies of the Sorbonne (IEDES). This “field” was marked by global political measures, the health crisis and the dizzying changes, of all kinds, caused by the pandemic of Coronavirus disease (COVID-19), provoked by the SARS-CoV-2 virus. This infectious agent has influenced all stages of my research work. From the preparation of the field, through my observations, questionnaires and interviews on site, to the restitution work, my first research work in France will have been marked by a pandemic than became a world event.